2021
DOI: 10.1007/s00261-021-03365-5
|View full text |Cite
|
Sign up to set email alerts
|

Vesical Imaging-Reporting and Data System (VI-RADS) for assessment of response to systemic therapy for bladder cancer: preliminary report

Abstract: Purpose The Vesical Imaging-Reporting and Data System (VI-RADS) criteria are expanding, providing fine differentiation of bladder wall layers involvement. We aimed to explore the feasibility of a novel categorical scoring, the Neoadjuvant chemotherapy VI-RADS (nacVI-RADS) for radiologic assessment of response (RaR), to define the spectrum of treatment response among patients with muscle invasive bladder cancer (MIBC). Methods Ten consecutive patients diagnosed with non-metastatic MIBC were prospectively enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 14 publications
(19 reference statements)
0
11
0
2
Order By: Relevance
“…Furthermore, MRI based on VI-RADS has the perspective applicability to be broadly used for follow-up in patients with BCa 23 . Two potential applications of MRI based on VI-RADS are assessment of responses to systematic therapy and risk assessment 24 and active surveillance. Active surveillance may be considered in patients with low risk NMIBC 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MRI based on VI-RADS has the perspective applicability to be broadly used for follow-up in patients with BCa 23 . Two potential applications of MRI based on VI-RADS are assessment of responses to systematic therapy and risk assessment 24 and active surveillance. Active surveillance may be considered in patients with low risk NMIBC 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence has suggested that nacVI-RADS categories correctly described the final radical cystectomy pathological findings, both for complete responders (pT0) and for patients defined as partial or minimal responders. Consequently, nacVI-RADS proved to accurately predict the response to therapy [5 ▪▪ ,56]. This evidence may have implications for BCa management and could suggest addressing specific patients with active surveillance, bladder sparing procedures or radical cystectomy.…”
Section: Clinical Applications and Trending Outlooksmentioning
confidence: 91%
“…Figura 4. Esquematización de la anatomía de la pared vesical y respectivas imágenes de resonancia magnética en imágenes T2W, DWI, ADC y DCE [51]. DWI may show a thickened hypointense line representing edematous mucosa.…”
Section: Panebianco Et Al Propone Una Clasificaciónunclassified
“…En un estudio similar 231 pacientes sometidos a RMmp para discriminar TMI y TNMI antes de Re-RTUV, logrando una sensibilidad, especificidad y AUC del 91.9%, 91.1% y 0.94 respectivamente. (46) Un metaanálisis que incluyó 1770 pacientes, (51) con una sensibilidad y especificidad agrupadas de 0.83 (IC 95% 0.70-0.90) y 0.90 (IC 0.83-0.95) con un área bajo de curva de ROC de 94% para la detección de lesiones que comprometen el detrusor, sin embargo, el análisis mostraba una alta heterogeneidad entre los estudios. Un metaanálisis más reciente, que incluyó 22 estudios y 5414 reportes de RNMmp, con una AUC 0.93 y con una sensibilidad de 89% y especificidad del 84% para detectar TMI lo que vuelve al VI-RADS una herramienta altamente precisa.…”
Section: Panebianco Et Al Propone Una Clasificaciónunclassified
See 1 more Smart Citation